Endonymiprinsippet og flerspråklige stedsnavn i Europa - Hanno Sandvik (Namn og Nemne)
It is common practice in Norway to refer to foreign places using endonyms. Although this endonymic principle may sound straightforward, it is complicated by the existence of plurilingual toponyms. This article argues that regional and minority languages must not be ignored when deciding which endonym(s) to use. This may be considered as a decolonisation of toponymy. The article sets out to (1) compare the available definitions of “endonym”, (2) map the occurrences and extent of living regional and minority language toponyms in Europe, (3) test how the Language Council of Norway currently handles such toponyms, (4) develop and apply an improved and consistent set of rules for the normalisation of foreign toponyms in Norway, and (5) give recommendations for how to refer to foreign plurilingual places in Norwegian.